Alternative Solutions to Preserve the Revealed Byzantine Antiquities at the Venizelou Metro Station of Thessaloniki. Issue 4 (19th May 2017) - Anagnostopoulos, C.; Sextos, A.; Bikas, D.; Stylianidis, K.; Angelides, D.; Avramidis, I.; Kyrkopoulou, K.
ABSTRACT: This article presents the methodological approach adopted to prioritize and comparatively assess alternative design solutions aimed to retain the Byzantine antiquities that were found during the construction works of the new city Metro main line, without cancelling the construction and operation at the Venizelou station in which they were found during excavation. It is shown, on the basis of cost over the respective benefit, that such a challenging engineering task is indeed feasible from both a technical and a financial viewpoint through a pragmatic compromise between the infrastructure logistics and the priceless nature of the archaeological findings. The particular feasibility study was the first of its kind made at a city and national level, it is deemed as a significant contribution to the public debate between the local and governmental authorities that essentially paved the way toward complex engineering solutions, innovative ideas, and fruitful interactions, which are currently at the heart of the public debate. Even though it is not seen by any means as the unique solution to the particular problem, it is considered as a useful contribution to the present state-of-the art of potential strategies that can be adopted by decision-makers in resolving a multiple-objective, dual engineering and archaeological problem.